Importance of the contingent claims analysis in detecting banking risks: Evidence from the Greek bank crisis - Constantinos Kyriakopoulos; Alexandros Koulis; Gerasimos Varvounis (Journal of Central Banking Theory and Practice, 2023)
In this paper we apply the Contingent Claims Analysis (CCA) to the banking sector in Greece with a particular focus on the years of the Greek debt crisis. Greece was selected primarily because its banking sector was hit hard due to the country's government debt default and its large exposure to domestic loans. The results obtained on the SIB's level and on the banking sector level gave us particular insight into the benefits of CCA for micro- and macroprudential policy reasons. The Distance-to-Distress (DtD) risk metric produced is particularly useful for detecting banks' vulnerabilities and resilience before they are revealed in the market. Moreover, the reduced volatility of DtD time series makes it an ideal candidate for tool predictions purposes and ultimately for policy reasons.
Keywords: G1; G2; G13; G32; G33; H63; 330; Distance-to-Distress; banking risks; Contingent Claims Analysis; Greek crisis